Characterization and application of fluorescent hydrogel films with superior mechanical properties in detecting iron(Ⅲ) ions and ferroptosis in oral cancer - Wen, Jinxi; Wang, Jian; Wang, Siqi; Zhou, Xingping; Fu, You (Frontiers in Bioengineering and Biotechnology, 2025)
A one-step hydrothermal method was applied to prepare carbon dots (CDs) with superior fluorescence properties using chitosan as a carbon source. The as-prepared carbon dots were then grafted onto a sodium alginate-gelatin hydrogel film to form a fluorescent hydrogel film (FHGF), emitting at 450 nm under excitation of 350 nm light. In comparison to the CDs, the fluorescence intensity of this film was maintained over 90.0% and the luminescence position remained basically unchanged, caused by the unchanged surface light-emitting structure of the CDs, due to the existence of electrostatic repulsion between the CDs and the hydrogel. Moreover, the tensile-stress of the fluorescent film with 1.0 wt.% of the CDs was increased by 200% to 10.3 Mpa, and the strain was increased from 117% to 153%. The above experimental results are attributed to the hydrogen bonding between the CDs and the sodium alginate-gelatin hydrogel from analyses of the FT-IR spectra. Interestingly, Fe3+ exerted a great quenching effect on this fluorescent film in the concentration range of 0–1.8 μM. The film can be basically used recyclically to detect Fe3+ in solution with a detection limit as low as 0.043 μM. In a word, this work demonstrated an enormous potential of carbon dots in fabricating mechanical and fluorescent properties of the hydrogel and proposed a new detection platform for Fe3+. In view of the promising Fe3+ detection capacity, this hydrogel film can also be applied in oral bacteria surveillance and semi-quantification of ferroptosis in oral cancer.